(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
Teaching Turkish is a subject that requires meticulousness both at home and abroad. Especially the courses, foundations, institutes and university departments that provide Turkish education abroad are of particular importance. Many resources have been developed and textbooks have been written in terms of teaching Turkish for foreigners over the years. In addition to the resource books used in teaching Turkish, there are websites that can help us and inspire the activities. Especially during the pandemic period, internet-based, visual resources and online tests have gained importance today, when classes are held online. Some websites, which have many content such as some activities, tests, worksheets and visual cards that the instructors can use directly or take as examples, facilitate the work of the instructors in this regard. In this paper, a compilation study was made of websites that have content related to teaching Turkish and Turkish literature. Keywords: Teaching Turkish to foreigner; teaching turkish; resources in teaching Turkish; web-based resources in Turkish teaching; Turkish web sites.